Expression and Purification of Tobacco PR-1a Protein for Function Analysis - LI, JIA; DU, LINFANG; LIU, XIN; DU, SIWEN; HUANG, XINHE; JIANG, JIAHONG (Asian Journal of Chemistry, 2010)
Pathogenesis-related proteins are assigned an important role in plant defense and in general adaptation to stressful environment. Although tobacco PR-1a is the first pathogenesis-related protein to be purified and characterized, its function is the least known of all PR-families. In the present study, coding sequence for tobacco mature PR-1a protein was amplified and subcloned in pGEX-5X-3 expression vector to overexpress soluble GST-PR1a fusion protein (42 kDa) in Escherichia coli. The cleaved PR-1a protein (15.5 kDa) was isolated after removal of GST-tag by Factor Xa. Purified recombinant GST-PR1a protein was used to prepare antiserum which can be used to detect the native tobacco PR-1 in the acidic extract of the TMV-infected leaves. Antifungal assay in vitro showed that both GST-PR1a and cleaved PR-1a proteins had antifungal activity against Phytophthora infestans, suggesting that the free N-terminus is not necessary for PR-1a in its antifungal activity. These results provide some clues for investigating the action mechanism of PR-1a.